EVALUASI NILAI PENYUSUTAN ALAT BERAT DENGAN METODE GARIS LURUS PADA JALAN BYPASS BANDARA INTERNATIONAL LOMBOK (BIL) MANDALIKA 2: Evaluation Of The Depreciation Value Of Heavy Equipment With The Straight Line Method In Bypass Road Lombok International Airport (BIL) Mandalika 2 - Hasyim, Hasyim; Sideman, Iao Suwati; Rohani, Rohani; Salehudin, Salehudin; Pratama, I Gede Putu Yogi (Ganec Swara, 2025)
Procurement of heavy equipment requires precise analysis to avoid financial losses. Losses are usually caused by the continued use of equipment condition and value have decreased. Ignorance of the decreasing value of the equipment becomes an obstacle when submitting a tender when the latest equipment price information is needed. Heavy equipment or all goods with economic value will have a decrease in economic value. This decrease in is called depreciation. Calculating the depreciation value is very important for future calculations to avoid losses and to determine the value of the equipment after use or within a certain period. This study analyzes equipment after the construction of the Mandalika 2 Bypass Road project. In this depreciation value analysis, the method used is the straight-line method using qualitative and quantitative data. The results of this study are shown in numerical form the depreciation that occurs will be higher if the equipment is in poor condition and will produce a lower value if the equipment is in good condition. The cost of equipment after a project is highly dependent on the depreciation value of the equipment. The higher the depreciation, the lower the price. If the depreciation value is calculated based on operational costs, it will be even higher.